Réforme de la taxe de vente - Watier, Régent (Assurances, 1989)
We wish to thank Mr. Régent Watier, Chairman of the Executive Committee and Chief Executive Officer of the accounting firm of Maheu Noiseux, for allowing us to publish his analysis of the federal sales tax reform. He examines the new system which will be a multistage sales tax, effective January 1, 1991, and the transitional steps to be taken before its implementation. ln particular, the author explains the mechanics of the new tax system and the effects of the current one. Mr. Watier concludes that such a reform is necessary.